A neurophysiological study of noun-adjective agreement in Arabic: The impact of animacy and diglossia on the dynamics of language processing. (May 2021) - Idrissi, Ali; Mustafawi, Eiman; Khwaileh, Tariq; Muralikrishnan, R.
Abstract: We used event-related brain potentials to identify the neurophysiological responses of Arabic speakers to processing full and deflected agreement in plural noun-adjective constructions in (written) Standard Arabic. Under full agreement, an adjective fully agrees in number and gender with a preceding plural noun; but this happens only when this noun is human. However, under deflected agreement, the adjective is marked feminine singular when the noun is non-human. We recorded grammaticality judgment and ERP responses from 32 speakers of Arabic to sentences violating full and deflected agreement and their well-formed counterparts. The participants were relatively fast and accurate in judging all the sentences, although violations, especially deflected agreement violations, were not always deemed ungrammatical. However, the ERP responses show a differential processing of human versus non-human violations. Violations of full agreement involving human nouns elicited larger N400 and P600 components than did violations of deflected agreement involving non-human nouns, whose ERP signatures were statistically identical to those of their acceptable counterparts. Our results present clear evidence for animacy (more specifically, humanness) effects on language processing and may also be taken to suggest possible effects of diglossia on the dynamics of language processing. We discuss these results in light of the ERP literature on agreement processing and the role of animacy/humanness in grammar, and the emerging results on idiosyncratic patterns of agreement as found in Spanish. Although it is not a central point in the paper, we discuss the potential effect of diglossia on the architecture of the mental grammar of Arabic speakers. Highlights: Noun-adjective agreement violations in Arabic elicited a biphasic N400–P600 effect. The effect was observed with human nouns, but not with non-human animate nouns. Long latency N400 due to processing complex morphology with humanness interaction. A late P600 suggesting reanalysis/repair routines. Animacy is highly salient, and diglossia may play a role in processing Standard Arabic.